2022
DOI: 10.1155/2022/9884006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatments and Orthodontic Bracket Type on Shear Bond Strength of High-Translucent Zirconia: An In Vitro Study

Abstract: Objective. Considering the increasing number of adults seeking orthodontic treatment, and the possible need for bracket bonding to monolithic zirconia restorations, knowledge about the preferred type of bracket (metal/ceramic) and the most efficient surface treatment is imperative to achieve acceptable shear bond strength (SBS). This study aimed to assess the effect of different surface treatments and orthodontic bracket types on SBS of high-translucent zirconia. Materials and Methods. Totally, 248 disc-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The rising demand for dental aesthetics has led to an increased number of individuals seeking orthodontic treatment, including adults with a history of fixed prosthetic treatments ( Babaee Hemmati et al, 2022 ). Orthodontic brackets are categorized as metal or ceramic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…The rising demand for dental aesthetics has led to an increased number of individuals seeking orthodontic treatment, including adults with a history of fixed prosthetic treatments ( Babaee Hemmati et al, 2022 ). Orthodontic brackets are categorized as metal or ceramic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because bur roughening exposes and create micropores on the zirconia substructure, which is different from other mechanical and chemical methods, such as air abrasion and hydrofluoric acid etching [ 11 ]. In vitro studies have shown that there is no significant difference in the SBS between metal brackets and zirconia crowns after air abrasion [ 10 , 14 ], tribochemical silica coating, or carbon dioxide laser irradiation compared with no surface treatment [ 10 ]. Although a higher bond strength has been reported when using air abrasion compared with using a soflex disc [ 16 ], this might be due to the smaller grit size in the solflex disc, which is insufficient to roughen the zirconia surface.…”
Section: Discussionmentioning
confidence: 99%
“…The factors affecting the adhesion of an orthodontic bracket to zirconia includes the bracket materials [ 9 , 10 ] and surface treatment conditions [ 4 , 10 17 ], comprising mechanical and chemical protocols. Mechanical surface treatments include polishing with a prophy cup and pumice [ 11 ], air abrasion with alumina oxide particles [ 11 , 14 , 15 ], surface roughening [ 16 ], and laser irradiation [ 10 , 13 ]. Moreover, chemical surface treatments include etching with various acids, such as orthophosphoric [ 14 ] and hydrofluoric acid [ 11 , 13 ], and primer application [ 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation